Challenges in Tea Plantation-Based Small Community Water Safety Plan Implementation – A Sri Lankan Experience - DT Udagedara; A.A.G.D. Amarasooriya; D.C. Herath; S.M. Rajapaksha; A. Kulathunge; P. Rajapaksha; G. Subasinghe; S.K. Weragoda; S.S. Garusinghe (Journal of Tropical Forestry and Environment)
This paper presents the challenges and scientific approach adopted to overcome those challenges for Rural WSP (RWSP) implementation for the water supply schemes (WSS) in the Sri Lankan Tea Plantation sector. Factors positively and negatively impacting WSP implementation were identified through a SWOT analysis. Pooled response of the Likert scale survey of WSP team members to evaluate the impact of each contributing factor. A Spearman correlation was conducted to evaluate the correlations. Survey results confirmed that top management engagement, availability of financial resources, organizational structure, clustered community, government regulations, quality certifications, and similar cultural practices positively impact the success of WSP implementation. Poor community awareness, learning culture, communication barriers, poor sanitation and hygiene practices, inadequate stakeholder relationships, inadequate resources, skills, and lack of accountability were the factors hindering the WSP implementation. Correlation analysis showed specific relationships namely, lack of accountability with inadequate resources and skills, availability of financial support with inadequate resources and skills, and lack of awareness with a lack of resources and skills. Converting the negative factors to positive ones will make the WSP application successful in another similar plantation-based WSS. The major lesson from this intrinsic research study is that socioeconomic and cultural factors in the tea plantation are equally important as the typical technical aspects of the WSP.